2002
DOI: 10.2337/diabetes.51.5.1629
|View full text |Cite
|
Sign up to set email alerts
|

5′ Flanking Variants of Resistin Are Associated With Obesity

Abstract: In contrast, in case/control and family-based study populations from Scandinavia, we saw no effect on BMI with either of these promoter variants. No association was seen with diabetes in any of the population samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
132
4
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 26 publications
13
132
4
1
Order By: Relevance
“…Several polymorphisms have been found in the promoter region of the resistin gene and it has been reported that one polymorphism, −420 C>G, was related to plasma resistin levels and diabetes [20,21,30]. In this study, we investigated the molecular mechanism underlying the effect of the −420G/C variation on the expression of the resistin gene.…”
Section: Discussionmentioning
confidence: 98%
“…Several polymorphisms have been found in the promoter region of the resistin gene and it has been reported that one polymorphism, −420 C>G, was related to plasma resistin levels and diabetes [20,21,30]. In this study, we investigated the molecular mechanism underlying the effect of the −420G/C variation on the expression of the resistin gene.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study identified a single nucleotide polymorphism in the RETN gene associated with resistin mRNA expression levels in human adipose tissue (Smith et al, 2003). Genetic variation in the RETN has been found in association with obesity (Engert et al, 2002) and type 2 diabetes (Ma et al, 2002;Wang et al, 2002). Obesity and diabetes related phenotypes, such as sum of skinfolds, leptin levels and percentage body fat, have been linked to this region on chromosome 19 (Chagnon et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…183 One resistin 5 0 -flanking polymorphism, À420C4G, has been analysed for association with obesity with conflicting results. 184,185 The À420C4G G/G genotype displays significantly increased basal promoter activity in adipocytes, and is associated with significantly higher resistin mRNA levels in human abdominal subcutaneous fat. 186 Furthermore, an ATG repeat in the 3 0 -UTR region of resistin has been associated with insulin resistance, but not with obesity.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%